Концептуальное представление понятий в "Толковом словаре живого великорусского языка" В. И. Даля - Юган, Н. Л.; Yugan, N. L.; Юган, Наталія Леонідівна (Фенікс, 2016)
Стаття присвячена лінгвокультурологічному аналізу характеру об’єктивації етнічних знань у «Тлумачному словнику живої великоруської мови» В. І. Даля. Розглядається вербальна репрезентація культурних концептів у тексті словника.

The article is devoted to the linguistic and culturological analysis of ethnic knowledge objectification character in the «Explanatory dictionary of vivid Russian language» by V. I. Dahl. Verbal representation of cultural concepts in the dictionary text is considered in the article.
Юган Н. Л. Концептуальное представление понятий в "Толковом словаре живого великорусского языка" В. И. Даля / Н. Л. Юган // Одеський лінгвістичний вісник. - 2016. - Вип. 8. - С. 126-130.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; лінгвокультурологічний аналіз; об’єктивація; етнічні знання; linguistic and culturological analysis; objectification; ethnic knowledge; verbal representation; cultural concepts; вербальная репрезентация; культурні концепти